THE EFFECT OF SOSIAL MEDIA INFLUENCE, CONTENT MARKETING, AND E-WOM TOWARDS ONLINE PURCHASE DECISIONS IN MATARAM CITY - Hidayat, Surahman; Suardana, I Made; Dewi, Nami Khatina (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2023)
This study aims to examine the Influence of Social Media Influencers, Content Marketing, and Electronic Word Of Mouth on online purchasing decisions in Mataram City. So that the variables in this study consist of 3 (three) independent variables, namely Social Media Influencers (X1), Content Marketing (X2), and Electronic Word Of Mouth (X3) and 1 (one) dependent variable, namely purchase decision (Y). Samples are taken using purposive sampling. The data collection technique in this study was using a questionnaire. Data obtained using questionnaires as many as 80 respondents. The data were analyzed using SPSS multiple linear regression test. The results of this study show that Social Media Influencers do not have a significant effect on purchasing decisions, while Content Marketing and Electronic Word Of Mouth have a significant influence on purchasing decisions. The results of the f (simultaneous) test variables Influencer social media, Content Marketing, and Electronic Word Of Mouth influence simultaneously (together) on purchasing decisions, while in the determination test obtained R square which means that the 3 independent variables have an influence of 53.3% of the dependent variables while the remaining 46.7% of variables are not included in this study.